Vermicompost and FYM Effects on Biogeochemical Performances of Andrographis paniculata Nees - Kumari, Aloka (Asian Journal of Chemistry, 2011)
Since time immemorial, village and ethnic communities have been using a medicinal plant, Kalmegh (Andrographis paniculata Nees.), mainly for liver tonic useful in hyperdispsia, buring sensation, wounds, ulcers, chronic fever, malarial and intermittent fevers, inflammations, cough, common cold, bronchitis, skin diseases, snake bite, leprosy, colic, flatulence, diarrhoea, dysentery, haemorrhoids etc. While the demand of kalmegh is increasing, it is mandatory to standardize the cultivation practices. The experiment was laid out in a randomized block design (RBD) with two parameters replicated thrice. As a result, comparative study FYM @ 15 t/hac and vermidose 5t/hac (cow dung + vegetable wastes + Eisenia foetida) recorded double yields. Significantly higher protein was observed under treatment of organic manure viz., 10 tonne/hectare with spacing 30 cm × 45 cm and its morphological study and its biogeochemical study have been done at different stages of plants. Present paper deals with the vermicompost treated and FYM effect on morphological, chlorophyll, sugar, reducing sugar, protein as well as alkaloids.